Correlation between invasive and non-invasive quantification of myocardial amyloid load in cardiac transthyretin amyloidosis. (14th October 2021) - Ungericht, M; Groaz, V; Messner, M; Zaruba, M.-M; Doerler, J; Lener, D; Stocker, E.-M; Mayr, A; Kroiss, A; Poelzl, G
Abstract: Background: Cardiac transthyretin (ATTR) amyloidosis is an infiltrative disease caused by the extracellular deposition of misfolded ATTR protein in the myocardium. Early disease recognition and accurate description of cardiac involvement are fundamental, as cardiac ATTR amyloidosis is associated with poor prognosis. Although endomyocardial biopsy (EMB) remains the gold standard in amyloid detection and typing, non-invasive imaging can provide an accurate diagnostic tool. Bone scintigraphy enables early disease detection with high accuracy. However, it remains to be determined whether the degree of cardiac tracer uptake on bone scintigraphy correlates with the extent of histologic amyloid burden in EMB. Aim: This single center observational study aimed to compare the histological amyloid load in endomyocardial biopsies with the quantification of cardiac tracer uptake on 99mTechnetium-3, 3-diphosphono-1, 2-propanodicarboxylic acid (99mTc-DPD) scintigraphy in cardiac ATTR amyloidosis. Methods: 23 patients with cardiac ATTR amyloidosis were enrolled. Diagnosis was obtained with a combination of invasive and non-invasive methods. Perugini score, mean left ventricular tracer uptake (LV uptake) and left ventricular to corpus sterni uptake ratio (LV/CS ratio) on 99mTc-DPD-scintigraphy were measured, while histological amyloid load was quantified as percentage of the analysed myocardial tissue using Sulfated Alcian Blue staining and the Fiji-ImageJ programme. Bivariate correlation and Pearson correlation coefficient were used to study the relationship between EMB and 99mTc-DPD-scintigraphy findings. Results: We found a statistically significant correlation between histological amyloid load and Perugini score (r=0.47 p=0.02), as well as between Perugini score and LV/CS ratio (r=0.31 p=0.046). Mean LV tracer uptake showed a trend for correlation with histological amyloid load (r=0.37 p=0.08), without reaching statistical significance. Conclusion: We found a correlation between the extent of histologic amyloid burden in EMB and the degree of cardiac tracer uptake on 99mTc-DPD-scintigraphy. Our results underline the reliability of 99mTc-DPD-scintigraphy as a surrogate of histological amyloid load in the diagnosis of cardiac ATTR amyloidosis. Possible implications for the assessment of prognosis are subject to future studies with a larger number of patients. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Pfizer